-y-4=-2
-y=-2+4
-y=2
Then y= -2
If y=-2
then:
x-2y= -3
x-2(-2)= -3
x+4= -3
x= -3-4
x= -7
2006-09-27 08:45:59
·
answer #1
·
answered by THE CAT 2
·
1⤊
0⤋
- y - 4 = - 2 - - - - - - - - -Equation 1
x - 2y = - 3 - - - - - - - - - -Equation 2
- - - - - - - - - - - - - - - -
Solving for y equation 1
- y - 4 = - 2
- y - 4 + 4 = - 2 + 4
- y = 2
-1y/-1 = 2/- 1
y coefficient is 1
y = - 2
The solution set is { - 2 }
Insert the y value into equation 1
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Check for equation 1
- y - 4 = - 2
- ( - 2 ) - 4 = - 2
2 - 4 = - 2
- 2 = - 2
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Solving for x equation 2
x - 2y = -3
x - 2( - 2) = - 3
x + 4 = - 3
x + 4 - 4 = - 3 - 4
x = - 7
The solution set is { - 7 }
Insert the x value into equation 2
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Check for equation 2
x - 2 y = - 3
- 7 - 2( - 2 ) = - 3
- 7 + 4 = - 3
- 3 = - 3
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
The answer is
y = -2
x = -7
2006-09-27 09:11:46
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
-y-4=-2
add 4 on both sides
-y=2
dived by -1 on both sides
y=-2
x-2y=-3
subsitute y for -2
x-2(-2)=-3
multiply
x+4=-3
subtract
x=-7
2006-09-27 08:47:16
·
answer #3
·
answered by ghostychick88 2
·
0⤊
0⤋
this is a problem that requires you to solve for one variable at a time. take the first equation -y-4=-2. add 4 to both sides of the equal sign. you get -y = 2. then divide by negative 1 to both sides to get y = -2. take y= -2 and substitute it into the y variable in the second equation like this: x-2(-2) = -3. simplify it into x +4 = -3. then subtract 4 to both sides. x= -7.
x = -7, y = -2
you can check your answer by plugging in -2 into the first equation. -(-2) - 4 = -2. or you can plug in -7 for x and -2 for y into the second equation. (-7) - 2(-2) = -3
Just remember the basics for multiplying and dividing positive and negative numbers:
(+)(+) = (+)
(+)(-) = (-)
(-)(+) = (-)
(-)(-) = (+)
2006-09-27 08:48:59
·
answer #4
·
answered by cs 3
·
1⤊
0⤋
substitution method
-y -4 = -2
+4 = +4
--------------
-y = +2
/
-1 -1
------------
y = -2
you should now be able to solve for x using y = -2
x -2 ( -2 ) = -3
x +4 = -3
-4 = -4
-------------
x = -7
now this is using the substitution method, and not addition subtraction method or determinance method.
2006-09-27 08:58:26
·
answer #5
·
answered by yehoshooa adam 3
·
0⤊
0⤋
from the first expression, -y-4=-2
-y=2
or y=-2
y= -2 in second eqn
ie x-2(-2)= -3
x+4= -3
x= -7
U don't just copy it. That will not help you.
u must understand the problem & try to do similar problems your self
2006-09-27 08:51:29
·
answer #6
·
answered by math 2
·
0⤊
0⤋
You use elimination.
add 4 to both sides on the first equation.
Now you have:
-y = -2 + 4
Divide both sides by -1
Now you have:
y = 2 - 4
So:
y = -2
Now substitute.
x - 2(-2) = -3
So now it's:
x + 4 = -3
Subtract 4 from both sides.
Now you have:
x = -3 - 4
So:
x = -7
Therefore, the answer is:
x = -7
and
y = -2
2006-09-27 08:46:51
·
answer #7
·
answered by Conor 3
·
0⤊
0⤋
y=-2
x=1
2006-09-27 08:43:17
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋